The importance of internet for SME internationalization / Muhammad Najib Nasarudin and Farhana Aishah Abd Latiff - Nasarudin, Muhammad Najib; Abd Latiff, Farhana Aishah (Faculty of Business and Management, 2014)
The small and medium-sized enterprises (SME) sector has an important role to play in developing economies not only in economic development, but also in poverty improvement and job creation. The sector faces a number of constraints especially in accessing finance, markets, training and technology. Access to business information services has been identified as one area that needs attention from governments and business services providers if the SME sector in developing countries is to achieve sustainable levels of growth and development. Accessing business information services has over the years been greatly enhanced with the emergence of various information and communication technologies. SMEs nowadays should aware of the important of the Internet in their business in order to help them growth internationally. The Internet will increasingly empower SMEs to participate in the knowledge economy by facilitating connectivity, helping to create and deliver products and services on a global scale, and providing access to new markets and new sources of competitive advantage to boost income growth.